2013
DOI: 10.5539/ijps.v5n4p60
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Role of Attachment Styles on the Relationship between Alexithymia and Interpersonal Problems in an Iranian Population

Abstract: The moderating role of attachment styles on the relationship between alexithymia and interpersonal problems was assessed in the present study. Eight hundred and twenty nine Iranian general populations (372 men, 457 women) who were living in Tehran were involved in this study. The participants were asked to complete three questionnaires including Adult Attachment Inventory, Toronto Alexithymia Scale-20, and Inventory of Interpersonal Problems. Results showed a significant negative correlation between secure att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 23 publications
4
11
0
Order By: Relevance
“…The coefficient of determination show that 27% of the variance of one variable is explained by the variation values of the other variable. This result is confirmed by previous studies (Besharat & Shahidi, 2013;Besharat, 2010;Zarei & Besharat, 2010;Vanheule et al, 2007).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The coefficient of determination show that 27% of the variance of one variable is explained by the variation values of the other variable. This result is confirmed by previous studies (Besharat & Shahidi, 2013;Besharat, 2010;Zarei & Besharat, 2010;Vanheule et al, 2007).…”
Section: Resultssupporting
confidence: 92%
“…Table 3 reveals that the degree of an adolescent's alexithymia can predict the level of the interpersonal problems encountered in relationships, thus accepting the hyphotesis: F (1, 155) = 58.85, p <.001. Therefore, the results of a previous study done by Besharat and Shahidi (2013) are confirmed. However, the predictive value of alexithymia is low (Adj.…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations